Les Dépravés de Dieu - Romain Simenel (Ateliers d'Anthropologie)
Is transgression a basic feature of the category “youth” in Morocco? How does the relationship with religion—in this case Islam—contribute to the distinction between social age categories? To what extent is the relationship with God different according to whether one is a “youth” or a “man of honour”? Discredited and even rejected by Islam, celibacy, especially if it is prolonged, would seem to provide the most relevant perspective for exploring the limits of what constitutes a youth. This article begins with an analysis of a celibacy-treatment ritual practiced in many regions in southwest Morocco (a ritual that allows the “youth” category to be defined from the angle of both gender relations and religious relations) and then develops a more general study of representations linked to male youth—particularly as they relate to “licit” life and divine judgement. It is then demonstrated that in southern Morocco, from the religious point of view, men are “born twice”. It is between these two “births”, biological birth and marriage, that youth is situated. It is a time of religious transgression when youths are subjected to the influence of the cheytan and the West before returning as better Muslims. As God’s depraved ones, these youths distance themselves as radically as possible from a prescriptive Islam in order to then make a stronger choice to embrace religion with all their heart and become men on the road to paradise by virtue of marriage.